Second-language acquisition and motivation: A literature review - Pat Goodridge (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
This literature review traces the development of motivation in second-language acquisition, a field that has evolved from basic associations between affective factors and second-language performance to nuanced approaches of how motivation is shaped by a learner’s subjective cognition. With this review, we see that motivation’s role has always been central to language learning, and the development of our understanding of this role has mirrored the development of our understanding of second-language acquisition’s psychological and cognitive aspects. Such understanding contributes to many areas of second-language pedagogy, developmental psychology, and applied linguistics, all of which are relevant to our practical research goals of maximizing student effectiveness in second-language learning.
Keywords: Motivation; cognition; second-language acquisition; attribution theory; ideal L2 self